The distant hours : a novel - Morton, Kate, 1976- (New York : Atria Books, 2010)
A long-lost letter arriving at its destination fifty years after it was sent lures Edie Burchill to crumbling Milderhurst Castle, home of the three elderly Blythe sisters, where Edie's mother was sent to stay as a teenager during World War II.
Keywords: Mothers and daughters -- Fiction; Family secrets -- Fiction; World War, 1939-1945 -- Evacuation of civilians -- Fiction; World War, 1939-1945 -- England -- Kent; Mother-daughter relationship -- Fiction; Secrecy -- Fiction; World War, 1939-1945 -- Evacuation of civilians -- Fiction; World War, 1939-1945 -- Kent (England); Family life -- Fiction; Domestic fiction